2019
DOI: 10.1002/jcp.28767
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the expression pattern of mTOR‐associated lncRNAs and their genomic variants in the patients with breast cancer

Abstract: The mechanistic target of rapamycin (mTOR) is a fundamental component of a signaling pathway that is involved in the pathogenesis of breast cancer via different mechanisms. This pathway is functionally linked with a number of small nucleolar RNA host genes (SNHGs). In the present project, we have searched for the expression quantitative trait loci (eQTLs) within SNHGs that are possibly involved in the pathogenesis of breast cancer. Following this in silico step, we have assessed expression levels of mTOR and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
(60 reference statements)
1
14
0
Order By: Relevance
“…Result of RT-qPCR was consistent with that of transcriptome sequencing (p < 0.05) ( Fig. 1b) while SNHG3 expressed higher in estrogen receptor/progesterone receptor (ER/PR) compared with ER/PR positive BC [24]. However, there was less study about SNHG3 in BC.…”
Section: Resultssupporting
confidence: 78%
“…Result of RT-qPCR was consistent with that of transcriptome sequencing (p < 0.05) ( Fig. 1b) while SNHG3 expressed higher in estrogen receptor/progesterone receptor (ER/PR) compared with ER/PR positive BC [24]. However, there was less study about SNHG3 in BC.…”
Section: Resultssupporting
confidence: 78%
“…SNHG5, a relatively novel lncRNA, was attached to more and more attention due to its distinct biological and clinical effects in human cancers. Concluding from current clinical investigation results, SNHG5 overexpression was detected in multiple human cancers, including glioma, 20,24 acute myeloid leukemia, 37 breast cancer, 25,28 melanoma, 15,39 colorectal cancer, 16,21 osteosarcoma, 17,40 hepatocellular carcinoma 30 and bladder cancer. 23 In these cancers, SNHG5 could serve as an oncogene in tumor size, pathological stage, recurrence rate and overall survival.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 89%
“…[25][26][27] Zahra et al also confirmed that SNHG5 was involved in cancer stage, overall grade, mitotic rate and tumor size in BRCA patients. 28 Notably, SNHG5 was detected to correlate with positive reaction of estrogen receptor, progesterone receptor and Her2/neu expression, 28 which were main subtypes of BRCA patients. 29 Besides, SNHG5 knockdown inhibited proliferation and induced apoptosis, cell-cycle arrest at G1 phases in BRCA cells.…”
Section: Breast Cancer (Brca)mentioning
confidence: 97%
“…Wang et al [ 33 ] found that SNHG3 silencing enhances apoptosis in triple-negative breast cancer (TNBC) cells through the miR-326/integrin α5 (ITGA5) axis and inhibits cell viability, migration, invasion and the Vav2/Rac1 signaling pathway. These results demonstrated that SNHG3 acts as an oncogenic lncRNA in breast cancer, which may represent a potential diagnostic biomarker or a novel therapeutic target for cancers [ 34 ].…”
Section: Lncrna Snhg3 Dysregulation In Human Cancersmentioning
confidence: 99%